They snooze, you lose : the educator's guide to successful presentations + CD - Burmark, Lynell, 1946- (Jossey-Bass, 2011)
" Presentation skills that that will captivate your audience every time. In today's increasingly visual world, the art of giving presentations is a much-needed talent. They Snooze, You Lose, provides a comprehensive guide made especially for teachers and administrators who want to become presentation 'stars' in their classrooms, at board meetings, or any time they are in front of an audience. Describes how to apply the author's proven CHIMES2 elements: connections, humor, images, music, emotion, stories, and senses. Contains a bonus DVD with premade slides, a study guide, and reproducible images. Burmark is the author of the best-selling book Visual Literacy : Learn to See, See to Learn. Includes key sections on the best ways to integrate technology into your presentations. New and seasoned educators alike will benefit from this fun and easy-to-read guide on building essential presentation skills."